Metabolic Syndrome Is Associated With Poor Cognition: A Population-Based Study of 70-Year-Old Adults Without Dementia. (6th July 2021) - Marseglia, Anna; Darin-Mattsson, Alexander; Skoog, Johan; Rydén, Lina; Hadarsson-Bodin, Timothy; Kern, Silke; Rydberg Sterner, Therese; Shang, Ying; Zettergren, Anna; Westman, Eric; Skoog, Ingmar
Abstract: Background: Individual conditions of metabolic syndrome (MetS) have been related to dementia; however, their combined impact on the preclinical stage is unknown. We investigated the associations between MetS and domain-specific cognitive function as well as the role of sociodemographic, cardiovascular, and genetic factors. Methods: Within the Gothenburg H70 Birth Cohort Study-Birth cohort 1944, 1131 dementia-free participants (aged 70 years) were examined during 2014–2016. MetS (central obesity plus at least 2 factors [reduced HDL-cholesterol, elevated triglycerides, blood pressure, or blood glucose]) was identified according to the International Diabetes Federation criteria. Five cognitive domains (memory, attention/perceptual speed, executive function, verbal fluency, visuospatial abilities) were generated after z -standardizing raw scores from 10 neuropsychological tests. Education, heart disease, claudication (indicating peripheral atherosclerosis), and apolipoprotein genotype were ascertained by trained staff. Data were analyzed with linear regression models. Results: Overall, 618 participants (55%) had MetS. In multiadjusted linear regressions, MetS was related to poorer performance in attention/perceptual speed (β −0.14 [95% CI −0.25, −0.02]), executive function (β −0.12 [95% CI −0.23, −0.01]), and verbal fluency (β −0.19 [95% CI −0.30, −0.08]). These associations were present only among individuals who did not carry any APOE -ε4 allele or were highly educated. However, among those with MetS, high education was related to better cognitive performance. MetS together with comorbid heart disease or claudication was associated with even worse cognitive performance than each alone. Conclusions: MetS is associated with poor attention/perceptual speed, executive function, and verbal fluency performance. Education, apolipoprotein E-ε4 allele, and comorbid cardiovascular disease influenced the observed associations.